2004
DOI: 10.1152/ajpregu.00003.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced thermogenesis mediated by GABA in the preoptic area of anesthetized rats

Abstract: Osaka, Toshimasa. Cold-induced thermogenesis mediated by GABA in the preoptic area of anesthetized rats. Am J Physiol Regul Integr Comp Physiol 287: R306 -R313, 2004. First published March 18, 2004 10.1152/ajpregu.00003.2004.-Bilateral microinjections of GABA (300 mM, 100 nl) or the GABA A receptor agonist muscimol (100 M, 100 nl) into the preoptic area (POA) of the hypothalamus increased the rate of whole body O 2 consumption (V O2) and the body core (colonic) temperature of urethane-chloralose-anesthetized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 29 publications
11
77
1
1
Order By: Relevance
“…6 B, 7). Heart rate and expired CO 2 both fell slightly, as described previously (Osaka, 2004). Vehicle injected into the same position in the CLPO in six of seven rats had no effect on any of these variables (Fig.…”
Section: Microinjection Of Bicuculline Into the Preoptic Areasupporting
confidence: 82%
See 2 more Smart Citations
“…6 B, 7). Heart rate and expired CO 2 both fell slightly, as described previously (Osaka, 2004). Vehicle injected into the same position in the CLPO in six of seven rats had no effect on any of these variables (Fig.…”
Section: Microinjection Of Bicuculline Into the Preoptic Areasupporting
confidence: 82%
“…The currently accepted model of thermoregulation is that both heat production and heat loss are under tonic inhibitory control by warm-sensitive preoptic neurons (Zhang et al, 1995;Chen et al, 1998;Nagashima et al, 2000;Osaka, 2004;Rathner et al, 2008;Tanaka et al, 2009), with those regulating heat production projecting to the DMH and those regulating heat dissipation projecting directly to the medullary raphé (Nakamura and Morrison, 2007;Morrison et al, 2008;Rathner et al, 2008). No significant output from the preoptic region has been attributed to coldsensitive cells.…”
Section: Tail Sympathetic Nerve Fiber Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoinjection mapping in POA subregions with inhibitory agents to evoke cold-defense responses has suggested that such inhibitory, descending projection neurons are distributed mostly in the medial POA (28,29), although some of these neurons controlling CVCs also might be distributed in the MnPO (29). Our previous results support a local POA mechanism for eliciting cold-defense responses in which cutaneous cool signaling from the LPBel activates GABAergic interneurons in the MnPO, which then inhibit the tonic activity of the inhibitory projection neurons in the medial POA that innervate neurons in the caudal brain regions, including the dorsomedial hypothalamus and rostral medullary raphe, whose activation leads to sympathetic cold-defense responses (8,27) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Exercises that combine movement with breathing, such as yoga, cause significant increases in brain levels of gamma-aminobutyric acid (GABA) post-workout 46 . One study demonstrated that the action of GABA in the mid-dorsal region of the POA causes an increase in the core temperature through stimulation of thermogenesis in brown adipose tissue 47 . Finally, the literature suggests that CNS plasticity may be induced by functional or motor tasks 48,49 .…”
Section: Discussionmentioning
confidence: 99%